Intersecting doublesex neurons underlying sexual behaviours in Drosophila melanogaster - Pavlou, H (2014)
In Drosophila, the functionally conserved transcription factor, doublesex (dsx), is pivotal to the specification of sexual identity in both males and females. One of its key dedicated roles involves regulating the development of a sexually dimorphic nervous system (NS) that underlies both male and female reproductive behaviours. Specific inhibition of the function of dsx-expressing neurons in males and females results in a global disruption of these sex-specific behavioural outputs. However, little is known about the functional organisation of this dsx circuit that encodes the potential to display these behaviours. Such investigations require the generation of a novel transgenic tool, capable of separating the function of dsx in the NS from that of the body. To achieve this, I generated a novel split-GAL4 dsxGAL4-DBD hemidriver by ends in homologous recombination. Coupling the novel tool with the pan-neuronal elavVP16-AD hemidriver, revealed spatial restriction of dsxGAL4-DBD/elavVP16-AD expression to dsx neurons only; enabling the realisation of novel patterns of dsx-expression in the peripheral NS. Next, the ability to elicit male-specific behavioural outputs upon activation of all dsx neurons formed the basis of a large behavioural screen aimed at parsing dsx circuitry into functionally distinct clusters. I utilised the novel dsxGAL4-DBD hemidriver to screen a large collection of extant enhancer trap lines (ETVP16-AD), for the elicitation of distinct sub-behaviours of male courtship. Here, I show that the activity of dsx-expressing clusters in: i) the brain (dsx-pC1, -pC2 and -pC3 collectively) regulate the early steps of male courtship (initiation, orientation and wing extension), ii) the pro- and mesothoracic ganglia (dsx-TN1 and -TN2) regulate the middle steps of male courtship (wing extension and possibly courtship song) and iii) the abdominal ganglia (dsx-Abg) regulate the late steps of male courtship (abdominal curling, attempted copulation and copulation). These data establish functional correlations between dsx clusters in distinct neuroanatomical foci and specific sub-behaviours of the courtship repertoire. Furthermore, the novel intersectional tool primed a collaborative study on female post-copulatory behaviours. We identified key sensory neurons in the female reproductive tract involved in initiating post-mating behaviours. Subsequent functional interrogations of dsx circuitry in the central NS revealed a subset of dsx-expressing neurons in the Abg that mediate changes in the female behavioural repertoire after mating. Characterisation of this relatively simple neural circuitry sheds light on the organisation of the fly brain. Ultimately, future studies will define principles of neural circuit operation, which may be similarly conserved in the nervous systems of higher animals.